Numerical analysis of anchor loss and thermoelastic damping in piezoelectric AlN-on-Si Lamb wave resonators. (27th August 2019) - Siddiqi, Muhammad Wajih Ullah; Fedeli, Patrick; Tu, Cheng; Frangi, Attilio; Lee, Joshua E-Y
Abstract: Even though many thin-film piezoelectric aluminum nitride (AlN) on silicon (Si) Lamb wave resonators have been proposed in the literature, little focus has been set on the modeling of the quality factors Q . Their Qs are associated with numerous dissipation sources, which are often difficult to separate from each other in experiments. Besides, the values of Q measured in experiments can largely deviate from sample-to-sample of the same design. In order to gain better insight into these issues, we have applied numerical models to estimate anchor losses and thermoelastic damping to a large set of AlN-on-Si resonators specifically designed to have significantly different Qs. The data set includes biconvex resonators of different curvatures (designed to reduce anchor losses), regular flat-edge resonators, and different electrode patterns. For the broad range of devices tested, we show that the computed values of Q agree well with the experimental data. In particular, the experimentally measured values of Q in regular flat-edge Lamb wave resonators are due to comparable contributions of the two types of losses.